Immigration, Search, and Loss of Skill - Weiss, Yoram; Sauer, Robert M.; Gotlibovski, Menachem (Journal of Labor Economics, 2003)
This article develops and estimates an on‐the‐job search model of the entry of highly skilled immigrants from the former Soviet Union into the Israeli labor market. The estimated parameters of the model, together with information on the wages of immigrants from earlier waves, imply that, on average, immigrants can expect lifetime earnings to fall short of the lifetime earnings of comparable natives by 57%. Of this figure, 14 percentage points reflect frictions associated with nonemployment and job distribution mismatch, and 43 percentage points reflect the gradual adaptation of imported schooling and experience to the local labor market.